A lógica das proibições probatórias - Silva, Fernando Muniz (2017)
The exclusionary rules was analyzed by the research in the perspective of a general theory of the norm, supported by the deontic logic. For the understanding of exclusionary rules as a normative phenomenon in a civil law system, the research sought the logical structure of norms, within a theory of prescriptive propositions, in the should be order. Realizing the hesitancy of the current doctrine on the subject, the research proposed a diagnosis of the main dogmatic difficulties to prevent the construction of a theory for the exclusionary rules. In order to overcome the dogmatic difficulties of the subject, the research proposed to reestablish basic concepts about probative procedure, source of evidence and instrumental procedure of evidence, to highlight the distinction between investigation activity and production of evidence in Court. For the same purpose, the research highlighted the logical difference between normatively prohibiting a conduct and establishing limits to an allowed conduct. Lastly, the research emphasized the substantial difference between principles and rules, and the possibility of occurrence of antinomies between these two kinds of juridical norms. The research reserved the term "exclusionary rule", in a civil law system, for the aprioristically obtainable result by the performance of the criterion of specialty, in the resolution of an antinomy occurring at the level of juridical rules, when a special exclusionary rule excludes an previous and general right of evidence, prohibiting the use of one or more instrumental procedure of evidence in a specific purpose